Assessment of epicardial adipose tissue thickness in patients with resistant hypertension. Issue 1 (February 2016) - Erdogan, Güney; Belen, Erdal; Sungur, Mustafa A.; Sungur, Aylin; Yaylak, Bariş; Güngör, Bariş; Akyüz, Şükrü; Satilmiş, Seçkin
Abstract : Objective: Recent studies have shown that epicardial adipose tissue (EAT) thickness is increased in patients with hypertension. In this study, we aimed to investigate the relation of EAT thickness with resistant hypertension (RHT). Participants and methods: Study participants ( n =150) were classified into three groups according to their office and ambulatory blood pressure measurements: RHT ( n =50), controlled hypertension (CHT, n =50), and normotension (NT, n =50). All patients underwent a transthoracic echocardiographic examination to measure EAT thickness. Results: Clinical and biochemical characteristics of the groups were similar, except the CRP level, which was significantly increased in hypertensive patients compared with patients with NT ( P <0.001). EAT thickness differed significantly between groups ( P <0.001). The highest values were obtained in the RHT group (4.64±1.24 cm), followed by the CHT (3.3±0.82 cm) and NT (2.6±0.76 cm) groups. Multivariate analysis indicated age, physical activity level, and EAT thickness as independent predictors of RHT. The optimal cut-off value of EAT thickness for detection of RHT was found to be 3.42 cm, with a sensitivity and specificity of 82 and 77%, respectively (AUC=0.87, 95% confidence interval 0.81–0.92, P <0.000). Conclusion: EAT can be effective on blood pressure by several mechanisms. In this study, for the first time in the literature, the association of EAT with RHT is reported.